2021
DOI: 10.3390/cancers13112842
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nucleolin as a Novel AEG-1-Interacting Protein in Breast Cancer via Interactome Profiling

Abstract: Breast cancer is one of the most common malignant diseases worldwide. Astrocyte elevated gene-1 (AEG-1) is upregulated in breast cancer and regulates breast cancer cell proliferation and invasion. However, the molecular mechanisms by which AEG-1 promotes breast cancer have yet to be fully elucidated. In order to delineate the function of AEG-1 in breast cancer development, we mapped the AEG-1 interactome via affinity purification followed by LC-MS/MS. We identified nucleolin (NCL) as a novel AEG-1 interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…245 Ncl also binds to telomerase reverse transcriptase (TERT) in the nucleoplasm and promotes its nucleolar localization, preventing cancer cells from senescence and maintaining cancer proliferation. 246 Furthermore, Lee et al 247 showed that Ncl combines with astrocyte-elevated gene-1 in breast cancer to promote the growth and metastasis of breast cancer cells. Increased ribosome biogenesis in cancer cells is closely associated with continuously activated RNA Pol I/III.…”
Section: Ribosomes and Cancermentioning
confidence: 99%
“…245 Ncl also binds to telomerase reverse transcriptase (TERT) in the nucleoplasm and promotes its nucleolar localization, preventing cancer cells from senescence and maintaining cancer proliferation. 246 Furthermore, Lee et al 247 showed that Ncl combines with astrocyte-elevated gene-1 in breast cancer to promote the growth and metastasis of breast cancer cells. Increased ribosome biogenesis in cancer cells is closely associated with continuously activated RNA Pol I/III.…”
Section: Ribosomes and Cancermentioning
confidence: 99%
“…Fibroblast growth factor-binding protein 1(FGFBP1), as an initiating factor of angiogenesis, can bind to broblast growth factor 1 and participate in the process of cell growth together (Tomaszewski et al, 2011). Nucleolin (NCL), an eukaryotic nucleolar phosphoprotein, is aberrantly expressed in a variety of cancers and has received extensive attention (Miranda et al, 2021, Thongchot et al, 2022, Lee et al, 2021. High expression of NCL can not only be used as an indicator of enhanced mitotic activity, but also has anti-apoptotic effects, increasing the proliferation and invasion of tumor cells (Bywater et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Protein of OMVs (50 μg) were precipitated by treating methanol/chloroform (Choi et al., 2021). Precipitated proteins were conducted by in‐gel digestion as previously described (S. Lee et al., 2021). The tryptic peptides were analyzed in LC‐MS/MS with Orbitrap Eclipse™ Tribrid™ mass spectrometer (Thermo Fisher Scientific) coupled with Ultimate™ 3000 UHPLC system (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%